2001
DOI: 10.1111/j.1749-6632.2001.tb03565.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Steroids, and Stimulant Sensitivity

Abstract: The current study investigated ovarian modulation of the locomotor response to cocaine in rats. Ovariectomy in females lowered the response to cocaine (10 mg/kg ip), whereas castration did not change that of males. The locomotor responses of prepubertal males and females to cocaine were similar. However, the postpubertal sex difference resulted from a fall in cocaine‐stimulated locomotion in males rather than a rise in females. Neonatal testosterone treatment of female rat pups decreased the response to cocain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 64 publications
2
24
3
Order By: Relevance
“…The present study, however, noted effects on ICSS responding using systemic prazosin at doses of 0.5 and 2.0 mg/kg; doses that do not alter basal locomotion in an activity chamber [22,36] or in swim tests of spatial learning [37]. Moreover, in the present study, cocaine at 5.0 mg/kg markedly increased PR responding for ICSS, but in other studies this dose of cocaine is at the threshold for increasing locomotion in adult male rats [38,39].…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The present study, however, noted effects on ICSS responding using systemic prazosin at doses of 0.5 and 2.0 mg/kg; doses that do not alter basal locomotion in an activity chamber [22,36] or in swim tests of spatial learning [37]. Moreover, in the present study, cocaine at 5.0 mg/kg markedly increased PR responding for ICSS, but in other studies this dose of cocaine is at the threshold for increasing locomotion in adult male rats [38,39].…”
Section: Discussioncontrasting
confidence: 48%
“…The present study, however, noted effects on ICSS responding using systemic prazosin at doses of 0.5 and 2.0 mg/kg; doses that do not alter basal locomotion in an activity chamber [22,36] or in swim tests of spatial learning [37]. Moreover, in the present study, cocaine at 5.0 mg/kg markedly increased PR responding for ICSS, but in other studies this dose of cocaine is at the threshold for increasing locomotion in adult male rats [38,39].The present findings add to a growing body of literature in which antagonism of α1-ARs diminishes the behavioral effects of psychostimulants such as cocaine, morphine, amphetamine, and nicotine. Prazosin has been to shown to attenuate the hyperlocomotion induced by cocaine and amphetamine [19,21,22,40] and to block the locomotor sensitization induced by repeated cocaine or amphetamine administration [19,41].…”
contrasting
confidence: 48%
“…Prior work confirms that males display place aversion or very modest preference for 10 mg/kg IP cocaine but strongly prefer higher IP doses (20 mg/kg; Nomikos and Spyraki 1988;Mayer and Parker 1993;Russo et al 2003b), whereas postpartum and virgin females prefer IP cocaine at lower doses (5-10 mg/kg; Russo et al 2003a, b;present study). This sharp gender contrast may be partially attributable to global endocrinological, physiological, and/or pharmacokinetic differences between males and females, previously proposed to underlie cycling females' heightened vulnerability to cocaine's motoric and motivational effects (Becker 1999;Kuhn et al 2001;Chin et al 2002;Hu and Becker 2003;Russo et al 2003a, b;Carroll et al 2004;. Notably, cocaine pharmacokinetics remain strikingly consistent across postpartum and cycling states following cocaine administration parameters similar to those used here (Vernotica and Morrell 1998;Wansaw et al 2005;see Dwivedi et al 1993 for recently parturient females).…”
Section: Discussionmentioning
confidence: 60%
“…Such a sex difference is well established in adult rats, and it has been attributed in large part to the potentiating effects of ovarian hormones in females (Becker, Molenda, & Hummer, 2001), whereas only minimal inhibitory effects of testosterone have been reported for males (Becker et al, 2001). Studies with cocaine have also found that sex differences emerge after puberty (Kuhn et al, 2001;Parylak et al, 2008), and prepubertal ovariectomy has been shown to decrease the behavioral effects of cocaine (Kuhn et al, 2001) and amphetamine (Forgie & Stewart, 1994) in adulthood. However, the effects of ovariectomy on drug responses in these studies were only examined in adulthood, so it is not clear whether lower circulating levels of ovarian hormones in adolescence contributed to age differences after amphetamine.…”
Section: Change In Activity To Second Administration Of Amphetaminementioning
confidence: 96%
“…This regulation likely develops in adolescence, as suggested by post-pubertal emergence of sex differences in sensitivity to cocaine (Kuhn, Walker, Kaplan, & Li, 2001;Parylak, Caster, Walker, & Kuhn, 2008) and by altered cocaine (Parylak et al, 2008) and amphetamine (Forgie & Stewart, 1994) sensitivity in adult female rats ovariectomized before puberty. Thus, to test whether differences in circulating ovarian hormones influence age differences in locomotor activity after amphetamine, we ovariectomized rats 6 days before amphetamine treatment either before puberty at P25, after puberty at P40, or in adulthood (P65).…”
mentioning
confidence: 96%